MicroRNA-181 Variants Regulate T Cell Phenotype in the Context of Autoimmune Neuroinflammation - Ghorbani, Samira; Talebi, Farideh; Chan, Wing Fuk; Masoumi, Farimah; Vojgani, Mohammed; Power, Christopher; Noorbakhsh, Farshid (Frontiers in Immunology, 2017)
Background: Recent studies have revealed that multiple sclerosis (MS) lesions have distinct microRNA (miRNA) expression profiles. miR-181 family members show altered expression in MS tissues although their participation in MS pathogenesis remains uncertain. Herein, we investigated the involvement of miR-181a and miR-181b in the pathogenesis of MS and its animal model, experimental autoimmune encephalomyelitis (EAE). Methods: miR-181a and -b levels were measured in the central nervous system (CNS) of patients with MS and mice with EAE as well as relevant leukocyte cultures by real-time RT-PCR. To examine the role of the miRNAs in leukocyte differentiation and function, miR-181a and -b mimic sequences were transfected into cultured primary macrophages and purified CD4+ T cells which were then analyzed by RT-PCR and flow cytometry. Luciferase reporter assays were performed to investigate the interaction of miR-181a and -b with the 3’UTR of potential target transcripts and the expression of target genes was measured in the CNS of EAE mice, activated lymphocytes and macrophages. Results: Expression analyses revealed a significant decrease in miR-181a and -b levels in brain white matter from MS patients as well as in spinal cords of EAE mice during the acute and chronic phases of disease. Suppression of miR-181a was observed following antigen-specific or polyclonal activation of lymphocytes as well as in macrophages following LPS treatment. Overexpression of miR-181a and -b mimic sequences reduced proinflammatory gene expression in macrophages and polarization towards M1 phenotype. miR-181a and -b mimic sequences inhibited Th1 generation in CD4+ T cells and miR-181a mimic sequences also promoted Treg differentiation. Luciferase assays revealed Suppressor of mothers against decapentaplegic (Smad)-7, as a direct target of miR-181a and -b. Conclusion: Our data highlight the anti-inflammatory actions of miR-181a and -b in the context of autoimmune neuroinflammation. miR-181a and –b influence differentiation of T helper cell and activation of macrophages, providing potential therapeutic options for controlling inflammation in MS.